Exploration of methods which increase the productivity of water in urban agriculture - Ramlall, Aveen (My University, 2018)
South Africa is stricken by erratic rainfall patterns which, combined with technical and socio-economic challenges, have given rise to food insecurity. Urban agriculture (UA) is considered as one of the promising agricultural practices that can address food insecurity in urban areas. However, if UA is successfully implemented at a large scale it will potentially trigger a drastic increase in potable water demands if it is the preferred source of water for irrigation. Considering that South Africa's fresh water resources are almost fully utilised it will therefore not be able to support this increase in potable water demands, the challenge is how to obtain alternative fit-for-purpose water for irrigation that will promote urban agriculture and thereby increase food production and enhance food security in urban and peri-urban environments. This study identified three alternative sources of water that can be exploited for irrigated urban agriculture. These sources are wastewater, greywater, and rainwater. A desktop review of the literature showed that rainwater is the most suitable source of fit-for-purpose irrigation water that can be used to meet the demands of UA. This conclusion was based on the fact that rainwater offers various advantages (such as a lower salinity, sodicity, and heavy metal concentrations) over wastewater and greywater. Field investigations of four in-field rainwater harvesting (RWH) techniques were implemented at the Siyakhana Food Garden which is an urban garden that serves the residents of Johannesburg. The four techniques, which included in-field RWH with catchment area covered with plastic sheeting (RWH 1 ), in-field RWH with hand compacted catchment area (RWH 2), ridge and furrow RWH with hand compacted catchment area (RWH 3) and ridge and furrow RWH with ridges covered with plastic sheeting (RWH 4 ). RWH 4 gave the highest water productivity values in terms of fresh produce yield and biomass of Broccoli.
A research report submitted in fulfilment of the requirements for the degree of Master of Science in Engineering. to the Faculty of Engineering and the Built Environment, University of the Witwatersrand,2018